Novel thermophilic genera Geochorda gen. nov. and Carboxydochorda gen. nov. from the deep terrestrial subsurface reveal the ecophysiological diversity in the class Limnochordia - Karnachuk, Olga V.; Lukina, Anastasia P.; Avakyan, Marat R.; Kadnikov, Vitaly V.; Begmatov, Shahjahon; Beletsky, Alexey V.; Vlasova, Ksenia G.; Novikov, Andrei A.; Shcherbakova, Viktoria A.; Mardanov, Andrey V.; Ravin, Nikolai V. (Frontiers in Microbiology, 2024)
The class Limnochordia harbors a single cultivated member, the mesophilic Limnochorda pilosa, which was isolated from a meromictic lake. Despite numerous molecular signatures reported in various ecosystems, the ecophysiological versatility of this deeply branched lineage of Firmicutes (Bacillota) remains poorly understood. The objective of this study was to use targeted cultivation, based on metagenome-assembled genomes from a deep terrestrial aquifer in Western Siberia, to isolate two new thermophilic members of the class. These isolates, described as Geochorda subterranea gen. nov. sp. nov. and Carboxydochorda subterranea gen. nov. sp. nov. within the Geochordaceae fam. nov., were capable of both anaerobic and aerobic respiration using fumarate and O2, respectively, with simple sugars as electron donors. The cultivated Geochordaceae have demonstrated fermentative growth and degradation of various polymers, including starch, maltose, maltodextrin, xylan, and chitin. The carboxydotrophic C. subterranea sp. nov. exhibited autotrophic growth via the Calvin–Benson–Bassham cycle, using CO, H2, and formate as electron donors and O2 as an electron acceptor, adding metabolic flexibility to the bacterium in the nutrient-depleted “deep biosphere” and supporting the possibility of aerobic metabolism in the deep subsurface. The broad physiological potential deciphered from physiological experiments and comparative genomic data explains the widespread distribution of uncultivated members of the class Limnochordia in various ecosystems, where they can oxidize complex organic substrates through both aerobic and anaerobic respiration, as well as pursue a chemolithotrophic lifestyle through the oxidation of H2 or CO.